Acceleration of breeding process of winter wheat while using the regulated conditions - B. I. Sandukhadze; M. I. Rybakova; G. V. Kochetygov; V. V. Bugrova; A. A. Morozov; E. K. Sandukhadze; R. Z. Mamedov (Зерновое хозяйство России)
The article gives the results of growing the generations of two hybrids F1 and F2 under the scheme combining the regulated and natural conditions, which are characteristic to the center of Non-Black Earth area. The scheme has got two stages. The first stage is to obtain the generation of F1. The seeds of hybrids are sown on F1 in the container in the terms of winter wheat sowing. Until the end of vernalization they are in natural conditions, and then they are placed for ripening in the greenhouse. The combinations are valued according to a phenotype and selective traits; a sorting out takes place. The second stage is to sow seeds on F2 in a heated soil greenhouse, after vernalization the heating is turned off and a further growing continues in natural conditions. The seeds selected from F2 lines for F3 are sent to the breeding plots of 1.5 m2 or they are sown in the autumn of the year. Some samples, which originated from F1 and F2 and were grown in the containers and in the heated greenhouses in 2012, were approved for the competitive Variety Testing in 2015.